2018
DOI: 10.1097/mnm.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET metabolic metrics and International Prognostic Score for risk assessment in HIV-infected patients with Hodgkin lymphoma

Abstract: There was no significant difference in F-FDG metabolic parameters, IPS, and other risk indicators between HIV-infected and HIV-uninfected patients with Hodgkin lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…This may be due to the fact that most of the HIV infected patients had good virologic suppression on anti-retroviral therapy. As we previously shown in patients with anal cancer and Hodgkin lymphoma, HIV-infection may be playing a limited role as a driver of aggressiveness in the ART era [28,29]. Regarding racial distribution of our study sample, we found the White population to be older compared with the Blacks with a difference tending towards a significant level.…”
Section: Discussionsupporting
confidence: 54%
“…This may be due to the fact that most of the HIV infected patients had good virologic suppression on anti-retroviral therapy. As we previously shown in patients with anal cancer and Hodgkin lymphoma, HIV-infection may be playing a limited role as a driver of aggressiveness in the ART era [28,29]. Regarding racial distribution of our study sample, we found the White population to be older compared with the Blacks with a difference tending towards a significant level.…”
Section: Discussionsupporting
confidence: 54%
“…Interim PET-CT after two or three cycles can be used to decide if less chemotherapy can be given according to the to the metabolic response. A retrospective study by Lawal et al showed the usefulness of fluorine-18-fluorodeoxyglucose PET (FDG-PET) performed at diagnosis to stratify PLWH and cHL, without differences in metabolic parameters between HIV-positive and HIV-negative patients [77]. A study by Okosun et al demonstrated the utility of an interim FDC-PET after two or three cycles to predict outcomes in PLWH with advanced stage cHL treated with BVD [78].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…The clinical symptoms include abdominal discomfort, bloody stools, abdominal masses and systemic symptoms, such as fever, night sweats, fatigue and weight loss. 13 Clinically, NHL is broadly classified as indolent and aggressive based on its clinical presentation and biological features. To more accurately determine the malignancy and prognosis of lymphoma, biological parameters are used as predictors, such as the Ki-67 index, erythrocyte sedimentation rate, LDH and b2 microglobulin.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The clinical symptoms include abdominal discomfort, bloody stools, abdominal masses and systemic symptoms, such as fever, night sweats, fatigue and weight loss. 13 …”
Section: Discussionmentioning
confidence: 99%